XIV session of German national college of gastroenterologists - A. A. Sheptulin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To generalize the reports submitted at the XIV session of German national college of gastroenterologists.Original positions. During session most actual issues of diagnostics and treatment of diseases of esophagus, stomach, liver, gallbladder, pancreas and intestine were considered. The statistical data on frequency and prevalence of gastroenterological diseases in Germany were presented.Conclusion. Acquaintance to data of German national college of gastroenterologists allows to conclude on its similarity to lectures presented at the last session of the Russian national college of gastroenterologists, however there are differences in style data presentation.